2022
DOI: 10.1101/2022.04.25.22274300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Autonomic Symptom Burden in Long COVID: A Global Survey of 2,314 Adults

Abstract: BackgroundAutonomic dysfunction is a common complication of post-acute sequalae of SARS-CoV-2 (PASC)/long COVID, however prevalence and severity rates are unknown.ObjectiveThe primary goal of this study was to assess the frequency and severity of autonomic symptoms in PASC. We also aimed to assess symptom burden in PASC though well-validated questionnaires, evaluate which pre-existing conditions are associated with an increased risk of developing autonomic dysfunction, and determine whether the severity of acu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Although it is possible that these conditions were present but unrecognized in some patients before they developed COVID-19, the fact that the majority reported that they were previously healthy suggests that these conditions may have been a consequence of COVID-19. These conditions have been highlighted in other studies of long COVID, [40][41][42][43][44][45] so it is important that clinicians are aware of common management strategies. [46][47][48] Fourth, patients in this cohort experienced significant functional impairment (Supplemental Digital Content 5, http://links.lww.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that these conditions were present but unrecognized in some patients before they developed COVID-19, the fact that the majority reported that they were previously healthy suggests that these conditions may have been a consequence of COVID-19. These conditions have been highlighted in other studies of long COVID, [40][41][42][43][44][45] so it is important that clinicians are aware of common management strategies. [46][47][48] Fourth, patients in this cohort experienced significant functional impairment (Supplemental Digital Content 5, http://links.lww.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include Gaze-evoked nystagmus (HP:0000640), Pericardial effusion (HP:0001698), and Exercise intolerance (HP:0003546) that are typically diagnosed using specialist examinations or medical history that may not be easily coded in structured EHR fields. Additionally, several common manifestations of long COVID, including dysautonomia (57) , are less documented in EHR data in part due to the difficulties in recognizing these illnesses clinically and the fact that relevant findings may not be well represented in structured fields including the OMOP data available in N3C.…”
Section: Discussionmentioning
confidence: 99%
“…Essa incapacidade, por sua vez, desencadeia insegurança e, consequentemente, distúrbios psiquiátricos secundários. [20][21][22][23][24][25][26] Por todos esses motivos, o reconhecimento precoce da síndrome Pós-COVID é de fundamental importância tanto para o seu portador, como para familiares, seu círculo profissional e social de convivência. Todos os indivíduos, após exposição ao SARS COV-2 e à imunização, que apresentem um ou mais sintomas relatados previamente, devem ser avaliados com atenção.…”
Section: Hachul Et Al Disautonomias Pós-covidunclassified
“…A correlação do início dos sintomas com exposição ao vírus ou à vacina, mesmo que o paciente tenha sido oligo ou assintomático, é de extrema importância, já que sintomas da síndrome Pós-COVID podem se iniciar entre dias e semanas após o contato com o vírus e durar muitos meses. 20,25 Um exame físico completo, cardiovascular, respiratório e neurológico é mandatório. Atenção especial deve ser dirigida ao estado nutricional, grau de hidratação, coloração de mucosas, frequência e padrão respiratórios, saturação de O 2 , presença de sarcopenia e acrocianose.…”
Section: Hachul Et Al Disautonomias Pós-covidunclassified